1983
DOI: 10.1039/p19830002077
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth study of the azidobenzophenone–anthranil–acridone transformation

Abstract: The title transformation, particularly the conversion of anthranils into acridones, is shown to be critically sensitive to temperature, solvent, substituent, and metal catalysts. Thus the conversion of 3-(p-tolyl) anthranil into an acridone gives a ratio of 2and 3-methyl derivatives varying from 0.6 : 1 to 4.7 : 1 with changing temperature and solvent. In other similar thermolyses, solvents (e.g. 1,2,4-trichlorobenzene) were incorporated into the product and traces of metals and their derivatives had a dramat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…[26] Ketone 1c [27] was prepared in 81 % overall yield by treatment of isatoic anhydride with N,O-dimethylhydroxylamine hydrochloride in aqueous ethanol to give the corresponding 2-aminobenzamide, which then was treated with 4-methoxyphenyllithium obtained in situ from butyllithium and 4-bromoanisole by literature procedures. [28] Alcohol 5 [29] was prepared in 87 % yield by standard reduction of the ketone 1b with NaBH 4 in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…[26] Ketone 1c [27] was prepared in 81 % overall yield by treatment of isatoic anhydride with N,O-dimethylhydroxylamine hydrochloride in aqueous ethanol to give the corresponding 2-aminobenzamide, which then was treated with 4-methoxyphenyllithium obtained in situ from butyllithium and 4-bromoanisole by literature procedures. [28] Alcohol 5 [29] was prepared in 87 % yield by standard reduction of the ketone 1b with NaBH 4 in ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…Meth-Cohn and co-workers reported 3-aryl-substituted anthranil 8 could be converted to an acridone 9 and 10 by exposure to a variety of different transition metal salts (Scheme 2). [6] In addition to acridones 9 and 10, aniline 11 was observed. The observation of aniline led the authors to implicate a metal nitrene as a reactive intermediate, which was formed upon cleavage of the N-O bond in anthranil 8.…”
Section: Isomerization Of Pre-existing N-heterocyclesmentioning
confidence: 96%
“…On the basis of these experiments, Gaunt and co-workers propose that the aryl C-H bond amination occurs through the reaction of polynuclear palladium species. Recently, Gaunt and co-workers reported that 2,3-disubstituted N-arylindolines 111 could be accessed if the diacetoxyiodobenzene oxidant was substituted with copper acetate [Equation (6)]. [52] Critical to the success of this transfor-…”
Section: Neutral Aminesmentioning
confidence: 99%
“…2,1-Benzisoxazoles (anthranils) are important compounds, particularly as starting materials for the synthesis of 2-aminoarylketones [ 1 4 ]. A number of heterocyclic systems, such as quinolines, acridines, or quinazolines, can be synthesized either from the latter or, in some cases, directly from 1,2-benzisoxazoles [ 1 10 ] (Scheme 1 ).…”
Section: Introductionmentioning
confidence: 99%